Assorted Facets of Ethics for Successful Business - H.S, Anitha; S., Kavitha (Ushus Journal of Business Management, 2009)
Ethics is a pedestal for any business to get good name and fame to endure for a long period in the competitive market. Code of ethics differs from one business to another, depending upon nature of the business. But for every business it is crucial and indispensable to follow ethical measures in its day to day business to enhance corporate ethical values to uplift or to promote ethical standards in an organization by bringing professional ethics and responsibilities among human resource of the company. Nowadays all the companies have made it mandatory to educate about ethics. Beyond that, they have started to practice it. As soon as an employee gets inducted to the company, a copy of the code of conduct will be given to him to understand the ethical values of the company and to follow it up.